2012
DOI: 10.2478/v10182-012-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression After Nacl Treatment in Two Tomato Cultivars Differing in Salt Tolerance

Abstract: SDS-PAGE electrophoresis was used to study the effect of NaCl on protein expression in two cultivars of tomato (Solanum lycopersicum L.): Edkawi (salt-tolerant) and Castle rock (salt-sensitive). Five-day-old seedlings were grown on MS agar media supplemented with 0, 50, 100, 150, 200 and 300 mM NaCl. Two days after treatment the seedlings were examined to determine the effect of salt on their growth and to relate that to protein banding variations. Gel analysis showed differences in at least 4 protein bands wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…According to the authors, the accumulation of RbcL at 50 mM NaCl in the cultivar Castle rock might be the result of Rubisco degradation under saline stress, as this cultivar is more sensitive to salinity. The better tolerance to salt stress of cultivar Edkawi is demonstrated by better retention of Rubisco content, chromosome segregation and up-regulation of ion pump proteins (Khalifa, 2012). In another study carried out on the cultivar BINATomato-5 the soluble protein content decreased by 25.64% at 60 mM NaCl and by 42.75% at 120 mM NaCl (Hossain et al, 2012).…”
Section: Salinity Effects On the Biochemical Parameters Of Tomato Pla...mentioning
confidence: 98%
“…According to the authors, the accumulation of RbcL at 50 mM NaCl in the cultivar Castle rock might be the result of Rubisco degradation under saline stress, as this cultivar is more sensitive to salinity. The better tolerance to salt stress of cultivar Edkawi is demonstrated by better retention of Rubisco content, chromosome segregation and up-regulation of ion pump proteins (Khalifa, 2012). In another study carried out on the cultivar BINATomato-5 the soluble protein content decreased by 25.64% at 60 mM NaCl and by 42.75% at 120 mM NaCl (Hossain et al, 2012).…”
Section: Salinity Effects On the Biochemical Parameters Of Tomato Pla...mentioning
confidence: 98%
“…Extensive studies in Brassicaceae family showed a positive correlation between salt stress and GLS content, [e.g. in broccoli (López-Berenguer et al, 2009), canola (Khalifa, 2012), radish sprouts (Yuan et al, 2010), pakchoi (Keling andZhujun, 2010)]. An increase in the signature of GLS content has also been reported for Brassicaceae taxa under drought stress, namey in Brassica napus (Champolivier and Merrien, 1997), Brassica oleracea (Radovich et al, 2005), Brassica rapa (Zhang et al, 2008), Brassica juncea (Tong et al, 2014), and Brassica carinata (Ngwene et al, 2017).…”
Section: Abiotic Stress and Gls Crosstalk In Brassicaceae: Wild Rockets As Emergent Taxamentioning
confidence: 99%
“…Proteins were extracted from 5-day-old seedlings after being soaked in the applied concentrations of 1, 0.5. 0.25, 0.125 and 0.0625 R of CS-PMAA-NPK NPs for 48 h as described by Khalifa (2012). Briefly, whole seedlings were ground in liquid nitrogen and then homogenized in Tris-HCl buffer (Sigma-Aldrich, St. Louis, MO, USA) at pH 8 (W/V); 0.1 mM phenylmethyl sulfonylfluoride (PMSF) as protease inhibitor and 100 mM dithiothreitol (DTT) as a reducing agent (instead of mercaptoethanol).…”
Section: Total Soluble Protein Extraction and Sds-page Electrophoresismentioning
confidence: 99%